Assessing the influence of the menstrual cycle on APT CEST-MRI in the human breast - Loi, Lisa; Görke, Steffen; Zimmermann, Ferdinand; Korzowski, Andreas; Meißner, Jan-Eric; Breitling, Johannes; Schott, Sarah; Bachert, Peter; Ladd, Mark E.; Schlemmer, Heinz-Peter; Bickelhaupt, Sebastian; Paech, Daniel (Magnetic resonance imaging, 2022)
Purpose: In fibroglandular breast tissue, conventional dynamic contrast-enhanced MR-mammography is known to be affected by water content changes during the menstrual cycle. Likewise, amide proton transfer (APT) chemical exchange saturation transfer (CEST)-MRI might be inherently prone to the menstrual cycle, as CEST signals are indirectly detected via the water signal. The purpose of this study was to investigate the influence of the menstrual cycle on APT CEST-MRI in fibroglandular breast tissue. Method: Ten healthy premenopausal women (19-34 years) were included in this IRB approved prospective study and examined twice during their menstrual cycle. Examination one and two were performed during the first half (day 2-8) and the second half (day 15-21) of the menstrual cycle, respectively. As a reference for the APT signal in malignant breast tumor tissue, previously reported data of nine breast cancer patients were included in this study. CEST-MRI (B1 = 0.7 mu T) was performed on a 7 T whole-body scanner followed by a multi-Lorentzian fit analysis. The APT signal was corrected for B0/B1-field inhomogeneities, fat signal contribution, and relaxation effects of the water signal and evaluated in the fibroglandular breast tissue. Intra-individual APT signal differences between examination one and two were compared using the Wilcoxon signed-rank test. The level of significance was set at p < 0.05. Results: The APT signal showed no significant difference in the fibroglandular breast tissue of healthy premenopausal volunteers throughout the menstrual cycle (p = 1.00) (examination 1 vs. examination 2: mean and standard deviation = 3.24 +/- 0.68%Hz vs. 3.30 +/- 0.73%Hz, median and IQR = 3.36%Hz and 0.87%Hz vs. 3.38% Hz and 0.71%Hz). Conclusion: The present study provides an important basis for the clinical application of APT CEST-MRI as an additional contrast mechanism in MR-mammography, as menstrual cycle-related APT signal fluctuations seem to be negligible compared to the APT signal increase in breast cancer tissue.
Gesehen am 01.03.2023